Dissipation Residue Behaviors and Dietary Risk Assessment of Boscalid and Pyraclostrobin in Watermelon by HPLC-MS/MS - Le Lv; Yue Su; Bizhang Dong; Wang Lu; Jiye Hu; Xiaolu Liu (Molecules, 2022)
Fungicides containing active ingredients of boscalid and pyraclostrobin have been widely applied in watermelon disease control. To provide data for avoiding health hazards caused by fungicides, we investigated its terminal residues and evaluated the dietary risk. In this work, watermelon samples were collected from field sites in six provinces and analyzed with high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). The average recoveries of boscalid and pyraclostrobin in the watermelon matrix were 97–108% and 93–103%, respectively, with the relative standard deviations (RSDs) ≤ 9.1%. The limits of quantifications (LOQs) were 0.01 and 0.005 mg/kg for boscalid and pyraclostrobin. Twenty-one days after applying the test pesticide with 270 g a.i./ha, the terminal residues of boscalid and pyraclostrobin were all below 0.05 mg/kg and below the maximum residue limits (MRLs) recommended by European Food Safety Authority (EFSA). According to the national estimated daily intake (NEDI), the risk quotients (RQs) of boscalid and pyraclostrobin were 48.4% and 62.6%, respectively. That indicated the pesticide evaluated in watermelon exhibited a low dietary risk to consumers. All data provide a reference for the MRL establishment of boscalid in watermelon for China.